Social Media Platforms’ Use in Building Stakeholder Relationships: The Case of National Sport Organizations - Gashaw Abeza; Norm O'Reilly (Journal of Applied Sports Management, 2014)
Social media has been widely touted by the popular media as an ideal tool to develop and sustain positive relationships between an organization and its stakeholders through the creation of dialogue. This research explores the validity of this claim via relationship marketing theory. The specific goal was to investigate how National Sport Organizations (NSOs) use their official Facebook and Twitter pages to create relationship dialogue with their stakeholders. A content analysis was conducted on the official Twitter and Facebook pages of 24 Canadian NSOs, and three hypotheses were tested. Results are contrary to the claims of those promoting social media, finding that Canadian NSOs’ Facebook and Twitter use did little to create a relationship dialogue. Results further note that NSOs preferred Facebook over Twitter.
Keywords: relationship marketing; relationship dialogue; interaction; communication; not-for-profit organizations